UPAYA PENINGKATAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG METODE KONTRASEPSI IMPLANT : UPAYA PENINGKATAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG METODE KONTRASEPSI IMPLANT - Istiyah, Istiyah; Suhaida, Suhaida; Sriningsih, Endang; Agustina, Lia; Novitasari, Dwi; Komalasari, Komalasari (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2023)
The implant is a hormonal contraceptive method in the form of a rod with a length of 4 cm which contains the hormone progesterone, the hormone will be released slowly which will work effectively as a contraceptive for 3-5 years, then from the start of use to 1 week it is recommended to use additional contraceptives such as condoms. Just like other hormonal contraceptives, implants can also affect the acceptor's menstrual cycle and can cause weight gain during use, the main side effects are spotting bleeding and amenorhea. (BKKBN, 2015). The implementation of this community service was carried out in the work area of Pasar Simpang Health Center in Simpang, Tanggamus Regency Lampung and was attended by 13 respondents of women of childbearing age. The methods used in this health counseling are lecture, discussion and question and answer methods. In this activity, pre and post tests were also conducted on respondents' understanding of contraceptives.